Perceived Ease of use on Purchasing Decisions in E-Commerce : a case study of TikTok social media - Tias Andarini Indarwati; Riska Dhenabayu; Ramadhan Maruta Pradana; Erta; Hapsari Shinta Citra Puspita Dewi (CV ODIS, 2023)
The ease of technology makes it easier for humans to do activities. The Tiktok Shop application has a positive impact on consumers shopping online. This convenience makes customers have high purchasing decisions to buy products. The reason for the high purchase decision is because there is a perception of convenience by the user. This research was based on the experience of TikTok Shop consumers aged 17 years and over. The method in this research uses qualitative case studies. Data collection techniques were carried out using interviews, observations, and documentation studies analyzed thematically. The results of this study indicate that the ease of technology in facilitating online shopping and purchasing decisions has increased with the various services available on the TikTok Shop application feature.